SOCIAL POLICY OF A TECHNICAL UNIVERSITY - Galina G. Batueva (Высшее образование в России)
The article considers the approaches to formation of social policy at technical university. Is shown that to achieve the main goal of the state social policy it is necessary to combine the efforts of the state and the efforts of all other subjects of the social sphere. It is offered to use the practice of social partnership for development and implementation of the social programs within the framework of the social policy carried out by the university. The established practices of social work allow to combine the efforts of social partners and to provide real effective help to university workers and students.